Efficacy assessment of different time cycles of nebulized hydrogen peroxide against bacterial and yeast biofilms. (September 2022) - Cobrado, L.; Ramalho, P.; Ricardo, E.; Fernandes, Â.R.; Azevedo, M-M.; Rodrigues, A.G.
Summary: Background: The prevention of healthcare-associated infections requires continuous effort. In order to achieve better practical results, the control of environmental microbial biofilms with effective disinfection strategies should be addressed. Aim: To test the efficacy of different time cycles of nebulized hydrogen peroxide (H2 O2 ) against bacterial and yeast dry biofilms. Methods: The efficacies of a standard cycle (SC) and a fast cycle (FC) of nebulized H2 O2 were compared. Microbial biofilms were grown on different material coupons. The metabolic activity of biofilms was determined by XTT assay, and the total biomass of biofilms was determined by crystal violet assay. Findings: Regarding the efficacy of nebulized H2 O2 against biofilms, the mean reduction in metabolic activity for the SC was 55.2% [standard deviation (SD) 19.4%], compared with 50.4% (SD 17.7%) for the FC. The mean reduction in total biomass for the SC was 45.5% (SD 22.7%), compared with 46.7% (SD 21.7%) for the FC. No significant differences were found between the tested cycles and materials. Conclusion: H2 O2 nebulization was found to exhibit good efficacy against healthcare-associated microbial dry biofilms. Moreover, similar efficacies were found between the SC and the FC.